Second-Person References in Netizens’ Comments on Lambe Turah’s New Instagram Post: Analysis and Implication - Budi Hermawan; R. Dian Dia-an Muniroh; Ni’matusy Syifa Auliya (Syntax Corporation, 2023)
Social media, particularly Instagram, has become a popular platform for users to interact and share information. One account that has attracted attention is